2011
DOI: 10.3109/14767058.2011.580401
|View full text |Cite
|
Sign up to set email alerts
|

Weaning of neonates from mechanical ventilation by use of nasopharyngeal high-frequency oscillatory ventilation: a preliminary study

Abstract: This small observational study demonstrates that nHFOV can be successfully applied to wean premature infants from ventilator support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 29 publications
5
49
2
Order By: Relevance
“…The absence of hypocapnia may seem surprising due to the reported ability of nHFOV to decrease CO 2 in newborn infants [6,7,21]. However, administration of nHFOV in these studies was for much longer periods than in our study, and the decrease in PaCO 2 was not apparent in the first 2 h [7].…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…The absence of hypocapnia may seem surprising due to the reported ability of nHFOV to decrease CO 2 in newborn infants [6,7,21]. However, administration of nHFOV in these studies was for much longer periods than in our study, and the decrease in PaCO 2 was not apparent in the first 2 h [7].…”
Section: Discussioncontrasting
confidence: 43%
“…Clinical interest in noninvasive HFOV stems from the fact that it does not require synchronization with the patient's breathing efforts [5]. In addition, HFOV is effective in eliminating CO 2 [6,7,21] while inducing less lung injury [3] and ensuring better alveolar development [8]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…73 Other observational studies revealed successful use of nHFOV as rescue therapy for nCPAP failure 74 and in the postextubation period. 75 To explore the future role that nHFOV could play in the treatment of RDS, further research on effectiveness and safety is needed.If rescue surfactant is administered without endotracheal intubation for more severe RDS, its benefits could possibly be combined with those of noninvasive respiratory support. Surfactant can be administered via a thin endotracheal catheter placed intratracheally by using a laryngoscope and a Magill forceps during spontaneous breathing and ongoing nCPAP treatment.…”
mentioning
confidence: 99%